(untitled) (Research, Society and Development, 2022)
Objective: To describe the participation of nursing in the screening of Postpartum Depression. Methodology: Systematic scope-type review using the Postpartum Depression descriptors. obstetric. Mental health. Methodology: The survey of articles was carried out on the Web, in two libraries and three databases: Virtual Health Library (VHL), CAPES journals portal, PubMed, Embase, Science Direct, guided by the guiding question: How does nursing participate in the screening for Postpartum Depression? From the year 2017 to April 2022. The evaluation of titles and abstracts was performed using a free Rayyan Qatar Computing Research Institute (Rayyan QCRI) web review software. Results: We found 689 articles, excluding 421 publications by titles, leaving 181 for reading abstracts and only 9 articles to be evaluated in full. Final considerations: Nursing must be present from prenatal to postpartum, participating in the establishment of the diagnosis of PPD, acting in the maintenance of breastfeeding, monitoring of women and their babies, and the interventions that are necessary for each woman. The nurse-mother bond is part of the nursing care that provides security for the woman and opens space for the expression of doubts and feelings, discomforts and preferences, fundamental elements both in the diagnosis and in the follow-up of each woman.